Bone histomorphometry of broilers submitted to different phosphorus sources in growing and finisher rations - Oliveira, Rafael Carvalho de; Costa, Luciano da Fontoura; Fernandes, Evandro Abreu; Alvarenga, Bauer Oliveira e; Matioli, Sérgio Russo; Beletti, Marcelo Emílio (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to identify alterations in the histomorphology of the cortical bone tissue of broilers submitted to growing and finisher rations formulated with five different sources of phosphorus: dicalcium phosphate, simple superphosphate, triple superphosphate, monoammonium phosphate and Araxá rock phosphate. Histological images had their components segmented, and were called regions of interest (ROI). Images were analyzed through developed algorithms, using the SCILAB mathematical environment. Eleven features were considered in order to obtain a complete description of the bone images: percentage of bone by area, ROI area, ROI perimeters, ROI elongation, ROI angle and their respective standard deviations, besides entropy of ROI angles and a texture-oriented measure (lacunarity). The substitution of dicalcium phosphate in growing and finisher rations for any other tested source of phosphorus caused significant changes on the hystomorphology of the cortical broilers bones, for example: diminution of bone percentage by area, increase of lacuna area and worse matrix homogeneity. Changes were more pronounced in the Araxá rock phosphate treatments, with the highest fluorine content, than in simple superphosphate, triple superphosphate and monoammonium phosphate treatments, which were similar.